Serological markers “CEA test & sAPRIL test” in Iraqi patients with colon cancer - Mahmood, Aqeel H.; Zeiny, Sarmad M.H.; Mahmood, Aqeel Sh. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Colonic cancer is a very common disease world-wide being fourth most common cancer characterized by abnormal proliferation of the inner wall of colon then taking full colon wall thickness then spreading to surrounding lymph nodes and tissues and finally distant metastasis. It is one of most complicated diseases with debilitating symptoms which becomes more sever , prominent and specific with advancing stage with high percent of fatality and relatively short survival if diagnosed late or if left untreated.Objective: To evaluate the efficacy of serum CEA & sAPRIL levels in the diagnosis and screening of colon cancer and their validity for this.Patients and methods: This study was applied on 35 patients with colonic cancer, 35 patients with benign polyps and 15 negative controls. All individuals were subjected to blood sampling for measuring their serum CEA & sAPRIL using ELISA technique.Results: In this study, majority of patients with colon cancer were presented at ages between 53-82 years of age (mean 68.5±6.4 years). Serum levels of sAPRIL & CEA were significantly elevated in those patients with advancing stages (C & D) compared with stages (A & B) and lower levels were found in patients who had surgical removal of tumor or received chemotherapy. Also a positive relation was found between sAPRIL & CEA with alcohol intake and smokingConclusion: according to this study sample it was found that sAPRIL and CEA together are strong indicators for colon cancer screening & diagnosis, and by this will reduce the need for more invasive screening & diagnostic tools.